2014
DOI: 10.4103/0971-6580.155331
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genotoxic potential of Hridayarnava Rasa (a herbo-mineralo-metallic ayurvedic formulation) using chromosomal aberration and sperm abnormality assays

Abstract: Objectives:Herbo-mineral formulations are being successfully used in therapeutics since centuries. But recently, they came under the scanner for their metallic contents especially the presence of heavy metals. Hence it is the need of the hour to assess and establish the safety of these formulations through toxicity studies. In line with the various toxicity studies that are being carried out, Government of India expressed the need for conducting genotoxicity studies of different metal- or mineral-based drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Previous studies revealed that N 1-MEQ exhibited adrenal toxicity in H295R cells ( Wang et al, 2016c ) and genotoxicity in mice ( Liu Q. et al, 2016 ). The connections of sperm abnormality with genotoxicity ( Jagtap et al, 2014 ; Devaux et al, 2015 ; Dong et al, 2015 ; Das et al, 2016 ; Liu W. et al, 2016 ) and sex hormones ( Liu W. et al, 2016 ; Cremonese et al, 2017 ; Ring et al, 2017 ) were well recognized. Commonly, alterations of sex hormones and steroidogenic pathways are associated with the function of the adrenal gland ( Sohn et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that N 1-MEQ exhibited adrenal toxicity in H295R cells ( Wang et al, 2016c ) and genotoxicity in mice ( Liu Q. et al, 2016 ). The connections of sperm abnormality with genotoxicity ( Jagtap et al, 2014 ; Devaux et al, 2015 ; Dong et al, 2015 ; Das et al, 2016 ; Liu W. et al, 2016 ) and sex hormones ( Liu W. et al, 2016 ; Cremonese et al, 2017 ; Ring et al, 2017 ) were well recognized. Commonly, alterations of sex hormones and steroidogenic pathways are associated with the function of the adrenal gland ( Sohn et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic Safe from genotoxic hazards 23 . Swasa kuthara rasa and smriti Inorganic Free from genotoxicity abnormality 24 .…”
Section: Hridayarnava Rasamentioning
confidence: 99%
“…Formulations like Swasa kuthara rasa, Smriti sagara rasa, Swarnamakshika bhasma, Hridayarnava rasa, and Tamra bhasma are reported to be free from genotoxic potential. [39][40][41][42] Though mercury is said to be a potent neurotoxin, Rasa sindhura and Kajjali are proven to be safe and free from toxicity on the Zebra fish behavior model. 43 All such studies on Ayurvedic formulations provided leads, emphasizing safety, efficacy, and usefulness of traditional systems of medicines.…”
Section: Studies That Have Proven Efficacymentioning
confidence: 99%